ANALYSIS OF FINANCIAL PERFORMANCE THROUGH SHARIA COMPLIANCE IN THE ISLAMIC BANKING - Yulianti, Lina; Karmila, Risma; Ruhimat, Ii (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to prove that financial performance is influenced by Sharia compliance in the Islamic banking industry. Multiple linear regression analysis uses panel data from the annual Sharia banking reports. Purposive sampling was used to select 40 samples of financial data from the Indonesian Sharia banking sector for four years, from 2019 to 2022. The results prove that Sharia compliance proxied by Islamic income ratio (IsIR), profit-sharing ratio (PSR), and Islamic investment ratio (IIR) has simultaneously impacted financial performance in Islamic banking. It is hoped that this research will help the government enhance the overall performance of Islamic banking. There are some recommendations for ‘Bank Indonesía (BI) or the Financial Servíces Authoríty to encourage profit-sharing financing by conducting workshops for Sharia banking and businesses to enhance the understanding and implementation of profit-sharing mechanisms. Strengthen regulations and standards for Sharia Compliance by mandating regular Sharia audits for Islamic banks to ensure continuous adherence to Sharia principles. Furthermore, Islamic banks' management must improve Shari’a compliance in banking applications because the higher the Shari’a compliance, the higher the public confidence in Islamic banking apps. It would help other interested parties and potential investors become part of the Islamic banking sector.